The Art of the Jesuit Mission in 16th-Century Japan: The Italian Painter Giovanni Cola and the Technological Transfer at the Painting Seminario in Arie: el pintor italiano Giovanni Cola y la transferencia tecnológica en el Seminario de Pintura de Arie - Montanari, Riccardo (Eikón / Imago, 2022)
The Jesuit Mission in Japan was characterized by the establishment of the first painting Seminario in the Far East supervised by the Italian Jesuit Painter Giovanni Cola, who arrived in Nagasaki from Rome in 1583. The activity of the painting school focused on the production of sacred images needed for the Missionaries' evangelization effort, and it soon became a hub of Renaissance technology. European pigments were made available to Japanese and Chinese painters who trained at the Jesuit facility. New archaeometric studies have enabled to present in this work, for the first time, a renewed interpretation of historical records, also revealing, along with documentary evidence, that Arie, a place located in Kyushu, where the Seminario stayed between 1595 and 1597, played a major role as it hosted the first European glass workshop in the Far East. The systematic use of pigments introduced at Arie influenced the production of scared images both in Japan and China. However, the overall technological transfer proved an asymmetrical process due to the fierce persecution of Christians from 1614, and, as a consequence, local production of imported pigments will not start until the lifting of the ban on Christianity in 1873 with the return of Europeans to Japan.